PENERAPAN TERAPI KOMPLEMENTER DENGAN TERAPI LAVENDER UNTUK MENGURANGI KECEMASAN PADA LANSIA DI DESA SIDODADI - Yanti, Mutiara Dwi; Siregar, GF. Gustina; Purba, Tetty Junita (Jurnal Pengabdian Masyarakat Putri Hijau, 2025)
Elderly individuals are prone to experiencing anxiety due to various physical, psychological, and social changes. In rural areas such as Sidodadi Village, Deli Serdang Regency, access to mental health services remains limited, making non-pharmacological interventions increasingly relevant. This community service program aimed to implement and eval_uate the effectiveness of complementary therapy using lavender aromatherapy in reducing anxiety among the elderly. The program was carried out through several stages, including initial coordination with village authorities, identification and screening of elderly participants, educational sessions for families and health cadres, and practical training on the use of lavender essential oil. eval_uation was conducted using a pre- and post-intervention design with anxiety scale measurements and knowledge tests. The results showed a significant decrease in average anxiety scores and a 35% increase in knowledge regarding anxiety management. Participants reported improved sleep, calmness, and emotional support from family members during the intervention. This program demonstrated that lavender aromatherapy is an effective, low-cost, and easy-to-implement complementary therapy that can enhance elderly well-being and can be integrated into community midwifery care. Further implementation at the Posyandu Lansia level is recommended for sustainability.